Les lieux incertains. - de Heusch, Lucio; Leblanc, Jean-Yves; Déry, Louise (Montréal : Éditions du département d'art plastiques Université du Québec, 1995)
de Heusch, Lucio ; duPont, Chantal ; Goulet, Michel ; Jean, Jocelyn ; Jolicoeur, Nicole ; Lavoie, Raymond ; Mongrain, Claude ; Régimbald-Zeiber, Monique ; Rousseau, Denis
boek